When More Poor Means Less Poverty: On Income Inequality and Purchasing Power - Andreas Bergh; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2012)
We show theoretically that the poor can benefit from price changes induced by higher income inequality. As the number of poor in a society increases, or when the income difference between rich and poor increases, the market for products aimed towards the poor grows and such products become more profitable. As a result, there are circumstances where an increase in poverty associates with higher purchasing power of the poor. Using cross-country data at two points in time on the price of rice and Big Mac hamburgers, we confirm the relationship between inequality and purchasing power of the poor, and show that it is robust to several control variables and also to a first-difference specification.
Keywords: D63; I30; 330; Income Inequality; Poverty; Purchasing Power